A Metric Analysis of a Human Cranium from the Khatystyr Cave, Republic of Sakha (Yakutia) - V. G. Moiseyev; A. V. Zubova; G. G. Boeskorov; K. Takase; A. D. Stepanov; T. A. Chikisheva; V. M. Dyakonov; A. N. Alekseyev; M. V. Shchelchkova; M. D. Tomshin; E. A. Kerbs (Archaeology, Ethnology & Anthropology of Eurasia, 2023)
We present the results of a metric study of a male Early Holocene cranium found in a cave near the Khatystyr village, Yakutia, in 1962. Eight measurements taken on the specimen were subjected to canonical discriminant analysis, using individual data on 14 ancient samples from Siberia and the Far East. Euclidean distances between these samples were calculated, and k-means clustering was performed. Results revealed similarity of the Khatystyr individual with Serovo crania from Cis-Baikal and with the Neolithic series from the Baraba forest-steppe. This suggests that the Khatystyr male is closely related to the earliest Upper Paleolithic populations of North Asia. A related component, assimilated by members of later migration waves, was also detected in other Northeast Asia territories, including Sakhalin, but is absent in the Neolithic samples from Primorye, in the Old Koryak and Old Bering Sea samples. Comparison with the Late Neolithic Ymyyakhtakh sample from Diring-Yuryakh, Yakutia, reveals no continuity between Early and Middle Holocene groups of that region. The Diring-Yuryakh sample shares no similarity with any other group, and likely represents an isolate.